Diagnosing Measurement Equivalence in Cross-National Research - Mullen, Michael R. (Journal of International Business Studies, 1995)
Many researchers have pointed out that it is necessary to ensure measurement equivalence in cross-national comparative research. Three aspects of measurement equivalence, translation, metric, and calibration equivalence, are necessary to establish the cross-national reliability and validity of items used to measure theoretical constructs. This paper discusses these issues and proposes two recently developed empirical techniques, Multiple Group LISREL and Optimal Scaling, for use in diagnosing cross-national measurement equivalence. These techniques are illustrated by reanalysis of a pioneering U.S. and Japanese study. The two techniques yield convergent results, indicating measurement equivalence for some, but not all, ordinal-level items under consideration. The findings demonstrate that the proposed methods are useful diagnostic tools for exploring measurement equivalence. Several suggestions for reducing the likelihood of problems with measurement equivalence and a number of methods for dealing with items where lack of equivalence persists are also discussed.